Evidence of STEM enactment effectiveness in Asian student learning outcomes - Bevo Wahono; Pei-Ling Lin; Chun-Yen Chang (SpringerOpen, 2020)
Abstract This study used a systematic review and meta-analysis as a method to investigate whether STEM enactment in Asia effectively enhances students' learning outcomes. Verifiable examples of science, technology, engineering, and mathematics (STEM) education, effectively being applied in Asia, are presented in this study. The study involved 4768 students from 54 studies. Learning outcomes focused on the students' academic learning achievement, higher-order thinking skills (HOTS), and motivation. The analysis results of effect sizes showed that the STEM enactments in Asia were effective at a moderate level (0.69 [0.58, 0.81 of 95% CI]) of improving students' learning outcomes. Sequentially, the effectiveness of STEM enactment starts from students' higher-order thinking skills, moves to students' academic learning achievement, and ends with the motivation. In addition, STEM enactments in Asia were carried out with several variations where STEM integrated with project-based learning was preferred. The recommendations of this study include a combination of the learning approach, learning orientation, and duration of instruction, all of which contribute to the STEM enactment effectiveness and maximize results in STEM education. Some practical implications, such as the central role of the teacher during the STEM enactment, are extensively discussed. This study supports that STEM education is a universally crucial tool which effectively prepares students from various national and cultural backgrounds, across Asia, toward improved learning outcomes.